2010
DOI: 10.1080/13102818.2010.10817893
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Cyclodextrin Glucanotransferase fromPaenibacillus MaceransATCC 8244 on Magnetic Carriers and Production of Cyclodextrins

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…For example, this technique retained 90% of its initial activity when incubated for 1 h at pH 9.0 and 50°C. The same preparation preserved its high catalytic activity after long-term storage at 4°C (60 days, 80%; Ivanova, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, this technique retained 90% of its initial activity when incubated for 1 h at pH 9.0 and 50°C. The same preparation preserved its high catalytic activity after long-term storage at 4°C (60 days, 80%; Ivanova, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…CDs possess both hydrophilic and hydrophobic properties that enable them to form specific inclusion complexes with many organic and inorganic compounds within the cavity of their ring structure (Pedersen et al, 1995;Atasanova et al, 2009). Consequently, the use of CDs increased annually by around 20-30%, of which 80-90% is used in food products (Ivanova, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This indicate that the enzyme structure no was affected. Ivanova [21] found that the optimum pH for CGTase from Paenibacillus macerans immobilized on magnetic nanoparticles was 7, which was the same as that for the soluble enzyme. Bruno et al [8] suggest that immobilization confers a kind of protection to enzymes, demonstrating different optimum pH for immobilized and soluble enzymes.…”
Section: Optimal Ph and Temperature And Thermal And Ph Stabilitymentioning
confidence: 94%
“…A similar finding is reported with CGTase immobilized on magnetic nanoparticles over seven cycles. However, Ivanova [21] using nanoparticles of magnetite as support for lipase immobilization obtained after 20 cycles [22]. According to Sheldona [23], the loss of activity in successive reuses reflects either the amount of linked CGTase on the carrier that is released into the assay solution or the loss enzyme function.…”
Section: Immobilization Efficiencymentioning
confidence: 99%